A Case of Focal Segmental Glomerulosclerosis in a Young Girl with a Very Low Birth Weight - Yasuyo Kashiwagi; Kazushi Agata; Gaku Yamanaka; Hisashi Kawashima (MDPI AG, 2022)
In Japan, the prevalence of low birth weight (LBW) has been estimated to be approximately 10%, which is the highest among developed countries. This high prevalence might affect the occurrence of LBW-associated diseases in the adult population of Japan. LBW has been recognized as a contributing factor to post-adaptive focal segmental glomerulosclerosis (FSGS) in adulthood; however, few reports to date have evaluated the clinical and pathological characteristics of post-adaptive FSGS. A 13-year-old girl was referred to our hospital owing to mild proteinuria, which was detected at a school urinary screening. She was born at a gestational age of 23 weeks, with a very LBW of 630 g. Dipstick urinalysis revealed grade (2+) proteinuria. Her serum creatinine level was 1.02 mg/dL, and she was diagnosed as having stage 2 chronic kidney disease (CKD). Her serum uric acid level was 7 mg/dL. Furthermore, her mother and 16-year old brother had hyperuricemia. A percutaneous renal biopsy leads to a diagnosis of FSGS. After 3 years of treatment with an angiotensin receptor blocker, her proteinuria decreased. However, her serum creatinine level was 1.07 mg/dL, and she still had stage 2 CKD. We considered that in this patient, the first hit was her LBW, and the second hit was hyperuricemia. The second hit might be associated with the development of CKD. The birth history of patients is not usually confirmed by nephrologists. Our case demonstrates that obtaining information regarding the preterm birth and LBW of patients is important in the diagnosis of noncommunicable diseases because school urinary screening is not routinely performed in countries other than Japan.